Sistem Informasi Penelitian dan Pengabdian Masyarakat di Universitas Mohammad Husni Thamrin : Sistem Informasi LPPM, Sistem Database LPPM, Rancang Bangun LPPM - Agustino, Rano; Widodo, Yohanes Bowo; Wiyatno, Agus; Saputro, Mohammad Ikhsan (Jurnal Jaring SainTek, 2020)
The Institute for Research and Community Service or Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) is an activity institution at the University Mohammad Husni Thamrin (UMHT) which functions to manage all research and community service activities. Every research conducted by lecturers aims to improve their quality in gathering tri dharma values, especially on research and community service. But at this time the processing of research data and community service to the LPPM UMHT has not used a database because the data processing uses excel and data archiving is still in physical form which can make it difficult to find data when the data is needed. Data management by using a database and a special application program is expected to be able to support an information system that is fast and accurate, so that the problem of time and the level of effectiveness in managing research data and community service can be optimized. In addition, the need for information from this institution is needed in a fast and appropriate condition to support the improvement of the quality of lecturers and others in terms of research and community service.